Integrated framework for design management and lean thinking in the fashion industry (ModaPalavra e-periódico, 2025)
The fashion industry faces increasing challenges in integrating creation and production practices efficiently and swiftly. In this context, design management and lean thinking emerge as complementary strategic approaches, capable of promoting waste elimination and enhancing production efficiency. However, the literature lacks integrative models that articulate both practices in a structured and replicable manner. This article proposes and validates an integrated framework for design management and lean thinking aimed at the fashion industry. The framework consists of three main phases: diagnosis, planning, and implementation, each subdivided into strategic activities focused on waste reduction and the optimization of design and production processes. The methodology is based on the principles of Design Science Research (DSR), which enabled the development and preliminary validation of the framework through its practical application in a fashion company located in Vale do Itajaí, Santa Catarina, Brazil. The results indicate a 20% reduction in rework, improvements in operational flow, and an increase in the prototype approval rate. These findings highlight the practical applicability of the framework, which can be replicated in other companies within the fashion sector. From a theoretical perspective, the article advances by proposing an integrative model that fosters greater synergy between design management and lean thinking, aligning creation, development, and implementation. Finally, it is suggested that future research validates the framework in companies of different sizes and regions, thereby broadening the generalization of the results.
Keywords: design management; lean thinking; integrated framework